PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER MELALUI EKSTRAKULIKULER PENCAK SILAT DI SMAN 1 KOTA SUKABUMI: PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER MELALUI EKSTRAKULIKULER PENCAK SILAT DI SMAN 1 KOTA SUKABUMI - Risandri, Irgi; Carsiwan; Rahmat, Alit (Universitas Negeri Medan, 2025)
This study aims to describe the instillation of character education values through extracurricular activities of pencak silat sports at SMAN 1 Sukabumi City. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of 25 students participating in the pencak silat extracurricular and the activity instructors. The results of the study indicate that in the implementation of the pencak silat extracurricular, the character values instilled include religious, honest, disciplined, hard work, creative, caring for the environment, and love of peace. The recapitulation of the observation results shows that the number of